Effect of an Antimalarial and a Micronutrient Supplementation on Respiration Induced Oxidative Stress - Iyawe, H.O.T.; Onigbinde, A.O. (Pakistan Journal of Nutrition, 2004)
This research was designed to access the effect of chloroquine a common antimalarial and ascorbic acid a popular antioxidant, on oxidative stress and liver function in animal models, with the aim of applying the research findings to the treatment of some devastating tropical diseases. A total of forty mice comprising of twenty males and females were divided into four groups per sex category and test drugs were administered intra peritoneally (ip) in mono and combined doses to healthy mice. Chloroquine treatment increased all oxidative stress indices with catalase being significant (P